The role of miRNAs in the invasion and metastasis of cervical cancer - Wang, Jin-yan (Biosci Rep, 2019)
Cervical cancer (CC) with early metastasis of the primary tumor results in poor prognosis and poor therapeutic outcomes. MicroRNAs (miRNAs) are small, noncoding RNA molecules that play a substantial role in regulating gene expression post-transcriptionally and influence the development and progression of tumors. Numerous studies have discovered that miRNAs play significant roles in the invasion and metastasis of CC by affecting specific pathways, including Notch, Wnt/β-catenin, and phosphoinositide-3 kinase (PI3K)-Akt pathways. miRNAs also effectively modulate the process of epithelial–mesenchymal transition. Many studies provide new insights into the role of miRNAs and the pathogenesis of metastatic CC. In this review, we will offer an overview and update of our present understanding of the potential roles of miRNAs in metastatic CC.